Evaluating the Soft Tissue Sarcoma Paradigm for the Local Management of Extraskeletal Ewing Sarcoma. (14th December 2020) - Boyce‐Fappiano, David; Guadagnolo, B. Ashleigh; Ratan, Ravin; Wang, Wei‐Lien; Wagner, Michael J.; Patel, Shreyaskumar; Livingston, John A.; Lin, Patrick P.; Diao, Kevin; Mitra, Devarati; Farooqi, Ahsan; Lazar, Alexander J.; et al.
Abstract: Objectives: We reviewed our experience treating patients with localized extraskeletal Ewing sarcoma (EES) to determine optimal local management strategies for this rare disease. Methods: Sixty patients with localized EES treated at our institution between 1994 and 2018 were reviewed. The Kaplan‐Meier method was used to estimates disease outcomes. Results: The median follow‐up time was 74 months (interquartile range [IQR], 17–121). Half the patients ( n = 30) received combined‐modality local therapy (CMT) with both surgery and radiation therapy (RT), whereas the other half received single‐modality local therapy (SMT) with either surgery or RT. All patients received chemotherapy. The 5‐year overall survival was 76%. Twenty‐two patients (37%) developed recurrence at a median time of 15 months (IQR, 5–56 months) resulting in 3‐year progression‐free survival (PFS) of 65%. On univariate analysis, the use of both neoadjuvant and adjuvant chemotherapy was associated with improved 5‐year PFS (71% vs. 50%, p = .04) compared with those who received one or the other. Furthermore, 11 patients (18%) developed local recurrences at a median time of 14 months (IQR, 2–19 months), resulting in a 5‐year local control (LC) rate of 77%. Use of CMT was not associated with improved LC (83% vs. 72% SMT, p = .41). Also, use of CMT was the only factor associated with poorer disease‐specific survival (vs. SMT; hazard ratio, 3.4; p = .047; 95% confidence interval, 1.01–11.4). Conclusion: For patients with EES, CMT was not associated with a decreased rate of local relapse. These data suggest that SMT alone may be sufficient for LC in select patients. A multi‐institutional collaborative effort should be considered to validate these findings. Implications for Practice: Extraskeletal Ewing sarcoma is a rare chemosensitive sarcoma whose clinical course more closely follows Ewing sarcoma of bone rather than that of other soft tissue sarcomas. Based on this study, combined‐modality local therapy did not confer a local control advantage compared with single‐modality local therapy. Therefore, single‐modality local therapy is likely adequate in select patients with favorable disease features, which has the advantage of ensuring prompt administration of systemic therapy. A multi‐institutional collaborative effort is warranted to determine which patients may benefit from de‐escalated local therapy. Abstract : Because extraskeletal Ewing sarcoma (EES) is a relatively rare clinical entity, there is limited data to guide optimal local therapy. Reporting a comparatively large single‐institutional experience managing patients with EES, this article evaluates outcomes of this rare disease and defines optimal local management strategies.